MEKANISME PENYUSUNAN RENCANA KERJA DAN ANGGARAN (RKA-SKPD) KANTOR KECAMATAN TAMBELANGAN KABUPATEN SAMPANG TAHUN ANGGARAN 2014 - Haryono, Haryono; Djasuli, Mohamad (Universitas Nusantara PGRI Kediri, 2016)
Work Plan and Budget Work Unit Strip (RKA-SKPD) is an important element in achieving the vision and mission of the District Public Sector Organizations, RKA-SKPD in Public Sector Organization Planning and Budgeting is a document that must be implemented by SKPD in the activities of the year which will be run. The aim of the study is RKA-SKPD Tambelangan Sampang District Office of Fiscal Year 2014. This study used a qualitative method with descriptive approach. The object of this study at the District Office Tambelangan Sampang. Data used in this study are primary and secondary data. Data collection procedures used are observation and interviews. Results from this study that the most important IPA, RKA-SKPD Tambelangan Sampang District Office of Fiscal Year 2014 was referred to the Minister of Home Affairs Number 13 Year 2006 on Regional Financial Management Guidelines